2012
DOI: 10.5539/jedp.v2n2p134
|View full text |Cite
|
Sign up to set email alerts
|

Change in Pupils’ and Students’ Attitudes toward School as a Function of Age – A Finnish Perspective

Abstract: The article describes changes in pupil and student contentment as a function of age in the general education system. School satisfaction was measured with a 216-item test with 15 different versions simultaneously in all grades of primary and lower secondary education and in two grades in upper secondary general education. IRT modeling with matrix sampling was used to equate the versions for all the grades. Pupil/student contentment decreased significantly after the 2nd grade with the intensity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Compared with the results on Metsämuuronen, Svedlin and Ilic (2012), the decline in the data, however, seems to be quite mild.…”
Section: Change In Achievement and Attitudes-a General Viewmentioning
confidence: 62%
See 3 more Smart Citations
“…Compared with the results on Metsämuuronen, Svedlin and Ilic (2012), the decline in the data, however, seems to be quite mild.…”
Section: Change In Achievement and Attitudes-a General Viewmentioning
confidence: 62%
“…The result of declining attitudes was expected because of the previous results (Metsämuuronen, 2006a;2006b;2006c;Metsämuuronen, Svedlin & Ilic, 2012). Compared with the results on Metsämuuronen, Svedlin and Ilic (2012), the decline in the data, however, seems to be quite mild.…”
Section: Change In Achievement and Attitudes-a General Viewmentioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, in a longitudinal study of Finnish students in grade 1 to grade 12 by Metsämuuronen et al (2012), it was concluded that student contentment in regard to school in Finland decreases significantly from the second to the eighth grade, while it then very slightly increases starting in the ninth grade. The majority (82% 11 ) of the Finnish students participating in the PISA are in the ninth grade, and almost all the rest are in the eighth grade (16%).…”
Section: Differences Between All the Global Clustersmentioning
confidence: 99%